Psychological mechanisms of metaphor, proverb and saying understanding by children - Firuza Z. Khayaleeva, Flera G. Mukhametzyanova, Leila M. Mukhtarova; Litvina, Lilya M. (Opción, 2019)
The article is devoted to the study of the psychological mechanisms for metaphor, proverb and saying understanding by children in English and Russian literature via theoretical and empirical methods. The testing of proverb understanding by children showed that all children (bilinguals and monolinguals) coped well with the assignment. However, the bilingual children coped with the test better than the monolinguals. After all, the authors concluded that the level of proverb understanding by children, both bilinguals and monolinguals, depends on the development and the manifestation of associative thinking and a child’s ability to see the meaning behind the images.